Graphical user interface for signal generator - Abu Bakar, Muhammad Lokman Al-Hakim (2007)
Graphical User Interface (GUI) for Signal Generator is a project MATLAB software base. Its objective is to generate signal using MATLAB and then can be verify using oscilloscope. MATLAB includes high-level commands for two-dimensional and three-dimensional data visualization, image processing, animation, and presentation graphics. GUIDE is the tools in MATLAB graphical user interface development environment, provides a set of tools for creating GUIs. The fundamental power of GUIs is that they provide a means through which individuals can communicate with the computer without rogramming commands. This project divides in two phase, software phase and hardware phase. Software phase, develop Graphical User Interface using MATLAB, interface boxes, syntax for user application to generate and display desired graphical signal. This MATLAB GUI-based program offer user only using mouse clicks (or possibly keyboard input) for any GUI element to display programmed wave form and generate signal. Hardware phase, develop hardware using MAX232 as an interface to pass information between output from computer to oscilloscope for measurement and comparison purpose. Output port is serial port using DB9 interface.